Real option valuation of game lodge concessions - J. Spencer-Young; F. Durand (South African Journal of Business Management, 2004)
Recent commercialisation of property in the Kruger National Park was achieved by the tendering of various concession rights. South African National Parks generated scenarios of possible future cash flows for private lodges on the concession sites and identified what rental incomes they expected to receive from the different concessions. Following the public tender of the concessions, they found that they had grossly underestimated the value of the concession rights as the actual tender values of the winning bidders far exceeded their mean concession fee valuations.Through the use of random stochastic modelling and Monte Carlo simulation this research shows that real option valuation accounts for the positive difference between the winning bids and the mean concession fee values for each of the concessions investigated.
Keywords: 650